The necessity of forming of interdisciplinary competencies for oil workers (Journal of Economic Research & Business Administration, 2016)
New scientific ideas arising in any sphere of human activity will not be recognized as innovations unless their realization brings a commercial interest. However, the sphere of market interest’s influence has its limits. The laws of the market such as the freedom to use the resources, freedom of choice, freedom of pricing are limited by legal, social, environmental and political laws and regulations. The violation of their requirements can lead to negative consequences for society, economy and state. Therefore, oil industry experts have all the right to possess basic knowledge and skills in the humanitarian field. The growth of experts’s competencies increases the efficiency of decision-making, enriches intelligence and personality, strengthens competitiveness in career growth.
Keywords: Interdisciplinary competence; oil industry expert; the format of the curriculum.